2016
DOI: 10.1177/0961203316643170
|View full text |Cite
|
Sign up to set email alerts
|

Complement levels and anti-C1q autoantibodies in patients with neuropsychiatric systemic lupus erythematosus

Abstract: Objective: The objective of this paper is to analyse serum levels of anti-C1q, C1q circulating immune complexes (CIC), complement activation and complement components in systemic lupus erythematosus (SLE) patients during the first central nervous system neuropsychiatric (NP) event and to define the possible association between these results and clinical and laboratory characteristics. Methods: A total of 280 patients suspected of having NP involvement due to SLE were recruited in the Leiden NPSLE-clinic. All S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 60 publications
2
18
1
Order By: Relevance
“…This acquired procoagulant state has traditionally been considered noninflammatory. However, recent evidence implicates complement activation in association with focal NPSLE, psychosis, and cognitive dysfunction, suggesting an added inflammatory pathogenic component. Mice deficient in C3 and C5 components of complement are resistant to aPL‐induced thrombosis and endothelial activation .…”
Section: Current Status Of Npslementioning
confidence: 99%
“…This acquired procoagulant state has traditionally been considered noninflammatory. However, recent evidence implicates complement activation in association with focal NPSLE, psychosis, and cognitive dysfunction, suggesting an added inflammatory pathogenic component. Mice deficient in C3 and C5 components of complement are resistant to aPL‐induced thrombosis and endothelial activation .…”
Section: Current Status Of Npslementioning
confidence: 99%
“…In previously published articles, abnormal serum complement components have been associated with a variety of autoimmune disorders, including multiple sclerosis [7], neuromyelitis optica [8,9], systemic lupus erythematosus [10], rheumatoid arthritis [11] and Crohn's disease [12]. Recently, Martinez-Hernandez et al [13] demonstrated the absence of complement components including C3, C9neo and C5b-9 in the brain of patients with anti-NMDAR encephalitis.…”
Section: Introductionmentioning
confidence: 99%
“…Several complement components have been associated with NPSLE: complement C3 with diffuse manifestations and complement C4 with focal NPSLE, although only with the concomitant presence of aPL. 26 Specifically, complement C5a may contribute to BBB dysfunction by inducing the production of pro-inflammatory cytokines, promoting reactive oxygen species formation, and prompting actin reorganization. 20 …”
Section: Physiopathologymentioning
confidence: 99%